2004
DOI: 10.1021/jp049107p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Colloidal CuInS2 Nanoparticles from a Molecular Single-Source Precursor

Abstract: Thermal decomposition of the molecular single-source precursor (PPh 3 ) 2 CuIn(SEt) 4 in the presence of hexanethiol in dioctylphthalate forms colloidal CuInS 2 at 200 °C. The colloidal solution displays size-dependent quantum confinement behavior in the absorption and photoluminescence spectra. The average size of the nanocrystals can be increased from 2 to 4 nm by raising the reaction temperature from 200 °C to 250 °C. The nanoparticles are capped with hexanethiol ligands; these ligands can be exchanged with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

22
432
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(458 citation statements)
references
References 64 publications
22
432
2
1
Order By: Relevance
“…Until now, the PL QYs of CIS/ZnS in the reach stage have been up to more than 80% [24,25,27,33]. Castro et al [17] reported a difference in the PL QY of two orders of magnitudes when applying different ligands. The strong effect on the optical properties has been assigned to the large number of defects on the surface of nanocrystals that provide a source of defects or unpassivated sites where nonradiative recombination takes place.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, the PL QYs of CIS/ZnS in the reach stage have been up to more than 80% [24,25,27,33]. Castro et al [17] reported a difference in the PL QY of two orders of magnitudes when applying different ligands. The strong effect on the optical properties has been assigned to the large number of defects on the surface of nanocrystals that provide a source of defects or unpassivated sites where nonradiative recombination takes place.…”
Section: Introductionmentioning
confidence: 99%
“…Several independent approaches for CIS synthesis were reported, for example, solvothermal synthesis [16], single-source precursor routes [17], and hot injection techniques [18,19]. An overview of the chemical synthesis methods for CIS or ternary compounds has been published by Kolny-Olesiak and Weller and Aldakov et al [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases, the uses of SSPs have granted control of both its physical and optical properties that dualsource precursors cannot [9][10][11]. In the last 20 years [12][13][14][15][16][17][18], many SSPs comprised metal (N,N-dialkyldithiocarbamates) [M(S 2 CNR 2 ) n ] have been used to synthesize metal sulfide nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…But, when it comes to nanoscale, the presence of multiple trap states and the lack of the knowledge about their ultrafast carrier trapping dynamics limit their efficiency in device-based applications. 16,[23][24][25][26] Various surface passivation techniques, e.g., treatment with different ligands or shelling with higher bandgap materials, have been tried to reduce the detrimental effects of surface-related traps. 24,[27][28][29][30][31][32][33][34][35] However, in order to design more efficient passivation strategies for photoactive materials for any applications, precise knowledge about the surface charge carrier dynamics is a prerequisite.…”
mentioning
confidence: 99%